The Influence of School Environment and Learning Motivation on Learning Independence in Deep Learning of Culinary Arts Students at SMK N 6 Semarang - Luthfiah Sis Nur Halim; Saptariana Saptariana (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2026)
This study falls within the field of vocational education, specifically examining student learning autonomy in deep learning at vocational high schools. The purpose of this study is to analyze the influence of the school environment and learning motivation on the learning autonomy of 11th-grade students in the culinary arts program at State Vocational High School 6 in Semarang. This study employs a quantitative approach with an ex post facto design. The study population consisted of 139 students, while the sample of 103 students was determined using the Slovin formula and proportionate random sampling. Data were collected through questionnaires and documentation, then analyzed using validity and reliability tests, descriptive analysis, classical assumption tests, simple regression, multiple regression, and the coefficient of determination. The results indicate that the school environment and learning motivation have a positive and significant effect on learning autonomy, both partially and simultaneously. Learning motivation has a more dominant influence than the school environment. Together, these two variables account for 58.7% of the variation in students’ learning autonomy. This study contributes to the development of vocational education research by emphasizing the importance of a supportive school environment and strengthening learning motivation in fostering students’ learning autonomy.